2012
DOI: 10.5334/ijic.691
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting a successful post-discharge outcome for individuals aged 80 years and over

Abstract: Introduction and backgroundThe early post-discharge period is a vulnerable time for older patients with complex care requirements. This paper identifies factors predicting a self-reported successful post-discharge outcome for patients aged 80 years and over by exploring factors related to the discharge process, the provision of formal home-care services, informal care and characteristics of the patients.MethodsThe study reports results from survey interviews with patients admitted from home to 14 hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
4
35
1
1
Order By: Relevance
“…In accordance with previous research focusing on older people in transition, this study shows that the patients wish to be involved and participate in the discharge process [9] [10] [15] [16]. Yet, lack of information and participation in the discharge process are reported in a range of studies [3] [11] [17] [23]- [25], supporting the findings in the current study. However, although the patients missed information and the chance to being better prepared before discharge from hospital, the older persons in our study accepted their situation and were grateful for the treatment they received.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with previous research focusing on older people in transition, this study shows that the patients wish to be involved and participate in the discharge process [9] [10] [15] [16]. Yet, lack of information and participation in the discharge process are reported in a range of studies [3] [11] [17] [23]- [25], supporting the findings in the current study. However, although the patients missed information and the chance to being better prepared before discharge from hospital, the older persons in our study accepted their situation and were grateful for the treatment they received.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were supported by Foss et al [16], who also indicate major shortcomings in participation, information and education in the discharge process. In a study of factors predicting successful post-discharge outcome, Bragstad et al [17] found that having someone at home upon return from the hospital and during formal home care services was significantly associated with patient-reported success in managing own health.…”
Section: Introductionmentioning
confidence: 99%
“…The patient questionnaire and Patients' perspectives have been reported elsewhere (Foss & Hofoss , Bragstad et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Current evidence suggests that older people at hospital discharge would benefit from better communication and more active participation of relatives in the discharge planning and that the discharge planning should start well ahead of the time of discharge (Bauer, Fitzgerald, Haesler, & Manfrin, 2009). Furthermore, it appears that the participation of relatives is a factor contributing to successful return to home (Bragstad, Kirkevold, Hofoss, & Foss, 2012). Little research has been carried out on the experiences of relatives in connection with the discharge from hospital of elderly family members, particularly to their own homes (Hvalvik & Reierson, 2015).…”
mentioning
confidence: 99%